Validity and correlates of the Brief Satisfaction With Appearance Scale for patients with limited and diffuse systemic sclerosis: Analysis from the University of California, Los Angeles Scleroderma Quality of Life Study. Issue 2 (June 2020) - Fox, Rina S; Mills, Sarah D; Gholizadeh, Shadi; Merz, Erin L; Roesch, Scott C; Clements, Philip J; Kafaja, Suzanne; Khanna, Dinesh; Furst, Daniel E; Malcarne, Vanessa L
Objective: The Brief Satisfaction With Appearance Scale measures two dimensions (Dissatisfaction with Appearance and Social Discomfort) of body image dissatisfaction in systemic sclerosis. This study examined the structural validity of the Brief Satisfaction With Appearance Scale across limited and diffuse systemic sclerosis subtypes, compared body image dissatisfaction by systemic sclerosis subtype, and identified the significant sociodemographic and medical correlates of body image dissatisfaction and whether they differed by subtype. Methods: Participants were 183 adults participating in the University of California, Los Angeles Scleroderma Quality of Life Study with limited cutaneous ( n = 101) or diffuse cutaneous ( n = 82) systemic sclerosis who received clinical examinations and completed questionnaires. Multiple-group confirmatory factor analysis, multivariate analysis of variance, and structural equation modeling were used. Results: The Brief Satisfaction With Appearance Scale's two-factor structure fit well for both subtypes. Patients with diffuse systemic sclerosis reported greater body image dissatisfaction on both factors than patients with limited disease. Greater Dissatisfaction with Appearance was associated with younger age and being unmarried for limited patients, and with younger age and increased finger/hand skin involvement for diffuse patients. Greater Social Discomfort was associated with younger age and being unmarried for both subtypes. Conclusion: The Brief Satisfaction With Appearance Scale scores can be meaningfully compared across limited and diffuse systemic sclerosis. Patients with diffuse disease reported more body image dissatisfaction than those with limited disease. Findings demonstrate that both medical and sociodemographic variables are associated with body image dissatisfaction in systemic sclerosis and can be used to identify which patients may be at increased risk for body image dissatisfaction.